2022
DOI: 10.54589/aol.35/2/134
|View full text |Cite
|
Sign up to set email alerts
|

Students’ perspective of the teaching-learning process of oral radiology before and during the COVID-19 pandemic

Abstract: The SARS-Cov-2 (COVID-19) pandemic changed the educational structure of dentistry courses and highlighted the importance of online tools. Understanding students’ perception regarding these changes is essential to establishing future teaching-learning strategies to accommodate students’ needs in higher education. The aim of this study was to assess students’ perceptions of the Oral Radiology teaching- learning process before and during the COVID-19 pandemic. The sample consisted of students (n = 111) of the 2nd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The findings of this study have some implications for teaching and learning and can be used as a policy input for the improvement of remote education. While research on the effectiveness of feedback to teachers from peers or traditional supervisors has provided conflicting results (Scheeler et al, 2004), questionnaire data from student feedback, as used for our analysis, can be one important feedback source to reflect on teaching and improve on instructional practices (Yang et al, 2021;R€ ohl and G€ artner, 2021;Costa-Neri et al, 2022). The present study showed that technology has great potential to take part in stimulating learning experiences, helped highlight stress levels among students and expanded proactive strategies, including strengthening policies and practices in the online education educational platform.…”
Section: Significance and Implications Of This Studymentioning
confidence: 80%
See 1 more Smart Citation
“…The findings of this study have some implications for teaching and learning and can be used as a policy input for the improvement of remote education. While research on the effectiveness of feedback to teachers from peers or traditional supervisors has provided conflicting results (Scheeler et al, 2004), questionnaire data from student feedback, as used for our analysis, can be one important feedback source to reflect on teaching and improve on instructional practices (Yang et al, 2021;R€ ohl and G€ artner, 2021;Costa-Neri et al, 2022). The present study showed that technology has great potential to take part in stimulating learning experiences, helped highlight stress levels among students and expanded proactive strategies, including strengthening policies and practices in the online education educational platform.…”
Section: Significance and Implications Of This Studymentioning
confidence: 80%
“…, 2004), questionnaire data from student feedback, as used for our analysis, can be one important feedback source to reflect on teaching and improve on instructional practices (Yang et al. , 2021; Röhl and Gärtner, 2021; Costa-Neri et al. , 2022).…”
Section: Discussionmentioning
confidence: 99%